Analysis of the Difference between INA-CBG Rates and Hospital Rates for Outpatient and Inpatient Services at FKRTL Provider BPJS Kesehatan Mataram City - Putu Gede Wawan Swandayana; Sastrawan Sastrawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The National Health Insurance Program or Jaminan Kesehatan Nasional (JKN) managed by the Health Social Security Administration Agency or Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS Kesehatan) has entered its eighth year of implementation. Since 2014, PT Askes (Persero) has transformed into BPJS Kesehatan, this also has an impact on changes in the payment system from Retrospective Payment System to Prospective Payment System with INA-CBG (Indonesian-Case Based Groups) rates. The difference between INA-CBG rates and hospital real rates is a fundamental problem, so hospitals must make efforts to achieve quality control and cost control. The real rate is the rate used by the hospital based on service of each service according to local regulations. Meanwhile, INA-CBG is a case-based health financing package by grouping various types of services into one unit. There is a difference between the INA-CBG rates and the hospital's real rates for paying JKN claims for Advanced Inpatient (RITL) and Advanced Outpatient (RJTL) services as a whole. This study is a descriptive-analytic quantitative research. The data used is secondary data obtained from the list of hospital JKN claims on the BPJS Kesehatan Claims Digital Verification application. The results of the study indicate that there is a negative difference between the total INA-CBG rate and the total hospital real rate for inpatient services of Rp. -25,654,787,895 or -36% of the INA-CBG rate. In outpatient services there is a negative difference of Rp. -6,144,370,328,- or -13% of the INA-CBG rate. Based on these findings, we recommend that hospitals should conduct a utilization review of health services, as well as calculate the appropriate unit cost for each type of service. The hospital carries out quality control of services by paying attention to the diagnosis and action and treatment provided, so that there are no unnecessary services.